Characterization of a Novel Rapidly Growing Mycobacterium Species Associated with Sepsis - Hong, Tao (American Society for Microbiology, 2003)
A rapidly growing mycobacterium was isolated five times from blood cultures from a 6-year-old female patient with relapsed pre-B-cell acute lymphocytic leukemia. All five isolates had identical nucleotide sequences for the first 500 bp of the 16S rRNA gene, indicative of a single species. High-performance liquid chromatography analysis of mycolic acids indicated that the species was similar to Mycobacterium smegmatis. Sequence analysis of the 16S rRNA gene (1,455 bp) for one isolate demonstrated that the species was closely related to Mycobacterium diernhoferi. Based on the phenotypic features and phylogenetic analysis, it was concluded that the isolates represented a novel rapidly growing Mycobacterium species. The name “Mycobacterium hackensackense” is proposed for this unique strain, 147-0552(T), which was deposited in the American Type Culture Collection as ATCC BAA-823(T).